(untitled) (Scientific journal of the Fergana State University, 2023)
In the study of the history and culture of Central Asian people at the end of the 19th and beginning of the 20th centuries, the eminent Russian scientists rendered great help and assistance to local Turkestan historians. There were founded one of the new directions of Russian oriental studies - Turkestan studies by the agency of local Turkestan historians at the end of the 19th century. In this article, basing on various types of archival sources, there have been presented little-known pages from the history of relations between prominent orientalist V.V. Bartold and famous Turkestanologist, N.S. Lykoshin, the expert of history, culture and ethnography of Central Asia.